Comparison of Post Dural Puncture Headache Occurrences During Spinal Anesthesia with 25g, 26g, and 27g Quincke Needles in Brachytherapy at Dr Sardjito Hospital, Yogyakarta - Trijayanti, Christiana; Mahmud, Mahmud; Sudadi, Sudadi (Jurnal Komplikasi Anestesi, 2026)
Background: Spinal anesthesia is one of the anesthesia techniques for surgery in various fields, one of which is brachytherapy. Post dural puncture headache (PDPH) is one of the most common complications after spinal anesthesia, one of the risk factors of which is related to the size of the spinal needle usedObjective: To determine the relationship between the incidence of PDPH after spinal anesthesia with Quincke needles with sizes 25G, 26G, and 27GMethods: The design of this study was an experimental study, randomized control trial and primary data collection was carried out on patients undergoing brachytherapy with spinal anesthesia in August-October 2024 until the sample size was met. The research data were tested using the Fisher's exact test and logistic regression.Results: 32 patients underwent brachytherapy with spinal anesthesia, with each group consisting of 44 patients. The highest incidence of PDPH occurred in the group with a 25G needle, namely 10 patients, and in the groups using 26G and 27G needles, there were 2 patients each who experienced PDPH. In multivariate analysis, BMI had a greater influence on the incidence of PDPH than the number of punctures, but there was no significant difference between the two variables.Conclusion: The use of 26G and 27G needles has a lower incidence of PDPH than the use of 25G needles